Shaun Hill: Salt is Essential, and Other Things I Have Learned from 50 Years at the Stove - Jaine, Tom (Petits Propos Culinaires, 2018)
Shaun Hill: Salt is Essential, and Other Things I Have Learned from 50 Years at the Stove: Kyle Books, 2017: 192 pp., hardback, £25.00.